ANALISIS YURIDIS PUTUSAN MK NOMOR 79/PUU-XVII/2019 TENTANG REVISI KEDUA UNDANG-UNDANG KPK: Juridical Analysis of Constitutional Court Decision No. 79/PUU-XVII/2019 Concerning the Second Revision of Corruption Eradication Commission Law - Ahmad Deni Rofiqi; Sholikul Hadi (Constitution Journal, 2023)
The Constitutional Court as the guardian of constitution is responsible for the implementation of fair national life as mandated by the 1945 Constitution of the Republic of Indonesia. As in the controversy over the second revision of the Corruption Eradication Commission Law, the Constitutional Court needs to be present to guarantee the process of drafting, discussing and ratifying a law to know whether it has complied with the constitution or not. Thus, the mandate given to the Corruption Eradication Commission can be carried out in a directed manner based on the laws of eradicating corruption in Indonesia. The study applied normative juridical research methods with statute approach, historical approach, conceptual approach, analytical approach and philosophical approach. The research findings showed that the Constitutional Judge's Decision which stated that the appellants’ arguments were groundless according to law could not be justified and the Corruption Eradication Commission was weakened through this second revision of law Keywords: Weakened, KPK, Constitutional Court Decision..   Mahkamah Konstitusi sebagai the guardian of constitution bertanggungjawab atas terselenggaranya kehidupan bernegara yang berkeadilan sebagaimana amanah Undang-Undang Dasar Negara Republik Indonesia 1945. Seperti dalam kontroversi revisi kedua Undang-Undang KPK, Mahkamah Konstitusi perlu hadir untuk menjamin proses penyusunan, pembahasan dan pengesahan suatu undang-undang telah sesuai dengan konstitusi. Sehingga, mandat yang diberikan kepada Komisi Pemberantasan Korupsi dapat dijalankan secara terarah berdasarkan undang-undang yang telah diatur untuk memberantas korupsi di Indonesia. Menggunakan metode penelitian yuridis normative dengan pendekatan undang-undangan (statute approach), pendekatan kasus (case approach), pendekatan historis (historical approach), pendekatan konseptual (conseptual approach), pendekatan analitis (analythical approach) dan pendekatan filsafat (philosophical approach) menghasilkan simpulan bahwa Putusan Hakim konstitusi yang menyatakan dalil para pemohon tidak beralasan menurut hukum, tak dapat dibenarkan dan lembaga KPK dilemahkan melalui revisi kedua Undang-Undang ini.    Kata Kunci : Dilemahkan,  KPK, Putusan Mahkamah Konstitusi.